Gaps in health research in the Dominican Republic - Julio Arturo Canario; Jefrey Lizardo; Roberto Espinal; Manuel Colomé
ABSTRACT Objective To provide a basic profile of health research in the Dominican Republic by identifying health problems or diseases that have been addressed by studies implemented during the period 2009-2013 and to determine how well that research correlates with the burden of disease in the Dominican population. Methods This was a descriptive study that searched for primary and secondary data sources to identify health research implemented in the Dominican Republic in the years 2009 to 2013. Data about these projects were collected from the registries of clinicaltrials.gov and the Consejo Nacional de Bioética en Salud, as well as from a questionnaire directed to researchers and managers. Disability-adjusted life years (DALYs) were derived from the Global Burden of Disease Study 2013 for males and females of all ages in the Dominican Republic and then compared with the number of research studies conducted on each specific health condition. Results This study identified 313 health research projects conducted in the Dominican Republic during the years 2009-2013. HIV/AIDS and lower respiratory infections were the two main topics researched; however, they accounted for a relatively small percentage of total DALYs in males and females of all ages in the Dominican Republic in 2013. Conclusions Limited research is directed toward addressing the health needs of Dominicans. The ongoing process of setting priorities for health research in the Dominican Republic should direct its efforts toward fixing this imbalance.